(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
Rheumatoid arthritis is an autoimmune inflammatory disorder, despite the discovery of numerous drugs there is still need to introduce newer, safer and more effective sources of drugs such as medicinal herbs. Present research work was an attempt to appraise the antiarthritic potential of Ribes alpestre Decne in rheumatoid arthritis. In vitro inhibition of protein (bovine serum albumin and egg albumin) denaturation, Human red blood cell membrane stabilization assays along with formaldehyde induced arthritis in rats were commenced in this study. Findings of present investigation demonstrated significant and dose dependent antiarthritic effect of Ribes alpestre. Aqueous ethanolic extract, butanol and aqueous fraction illustrated 95%, 69.233% and 92.840% protection at 6400 ug/mL against bovine serum albumin denaturation respectively. Similarly, plant extract together with butanol and aqueous fractions showed 3653.47%, 1484.03% and 3563.19% inhibition of pathological alteration of egg albumin in that order. Moreover, hydroethanolic extract with butanol and aqueous fraction exhibited 91.29%, 65.73% and 89.62% stabilization against erythrocyte hemolysis at 6400 ug/mL correspondingly. Furthermore, hydroethanolic extract, butanol and aqueous fraction notably 73.49%, 66.42% and 68.87% decreased paw edema at highest dose (200 mg/kg). Similarly aqueous ethanolic extract, butanol and aqueous fraction illustrated 72.38%, 54.90% and 66.33% decrease in paw thickness at 200 mg/kg. Hence results suggested that Ribes alpestre possess antiarthritic potential thus supporting its use as natural remedy in rheumatic conditions.